Perforation of a side branch of coronary artery during coronary angiography: A rare complication - Sihag, Bhupendra Kumar; CR, Pruthvi; Prasad, Krishna (Journal of Cardiovascular Medicine and Cardiology, 2020)
Coronary angiography in current day scenario is a very safe procedure. Complications are very rare occurring in less than 1 % of cases. We report a case of coronary artery side branch perforation during angiography. Injection of contrast into a side branch following accidental super selective intubation, lead to the perforation at the tip and contrast extravasation. Patient was managed conservatively as he did not develop any hemodynamic compromise or pericardial effusion. Check angiography showed no leak from the perforation site and he was discharged after 72 hours. Pressure tracing should always be monitored during angiography and dye injection should be stopped on super-selective intubations of the branches.